5. Changes in the role of the father in the 20th and 21th century - Walasek, Stefania; Jurczyk-Romanowska, Ewa (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2014)
„Wychowanie w Rodzinie” (“Family Upbringing”) is a journal dedicated to the problems of the family in the historical and the contemporary approach. The published original articles – written by authors from Poland and other countries who discuss research results as well as theories – constitute a voice in humanities and social sciences discourse on the family. Although the majority of the published papers belong to such branches of social sciences as history of education and pedagogy of the family it is increasingly often that the work of scholars of other sub-disciplines of pedagogy as well as psychology, sociology, archaeology, literary studies, linguistics, and law is presented.
Keywords: family; upbringing; children; history of upbringing